Tingkat Pengetahuan, Sikap, dan Perilaku Warga Kecamatan Ngaliyan Mengenai Nevus Pigmentosus - Puguh Riyanto; Danisa Diandra Safarina; Dini Hisan Wijdani; Cindy Cindy (Pusat riset dan Inovasi Nasional, 2025)
Nevus pigmentosus is a benign skin lesion that originates from the proliferation of melanocytes and has the potential to develop into melanoma, one of the most dangerous skin cancers. This study aims to evaluate the level of knowledge, attitudes and behavior of the people of Ngaliyan District regarding nevus pigmentosus. The design of this research is descriptive observational with a quantitative approach. Data was collected through questionnaires from 40 respondents using techniques convenience sampling. The results showed that 50% of respondents had good knowledge, 55% had a positive attitude, but only 47.5% had good behavior towards preventing and treating nevus pigmentosus. No significant relationship was found between age and gender on behavior, as well as between knowledge and attitudes on behavior. These findings indicate the need for increased education and health promotion to encourage better preventive actions in society.